Analisis Sisitem Pemberian Kredit Perumahan Krama (Krura) Dengan Prinsip Ringankan Krama 'Mipil" Pada LPD Desa Adat Kedonganan - Nugraha, K; Atmadja, Anantawikrama Tungga (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2020)
This study aims to determine: (1) how the background of the Kredit Perumahan Krama (Krura) was launched by the LPD of the Desa Adat Kedonganan, (2) how was the process of analyzing the giving of the Kredit Perumahan Krama (Krura) by the LPD of the Desa Adat Kedonganan, and (3) how the impact the provision of Kredit Perumahan Krama (Krura) for the krama Kedonganan Adat Village and the LPD Desa Adat Kedonganan. This research was conducted in the LPD Desa Adat Kedonganan, Kuta District, Badung Regency. This study used descriptive qualitative method. The data used in this study are primary data and secondary data. The results of this study stated that: (1) Kredit Perumahan Krama (Krura) was first launched at the end of 2018 to coincide with anniversary of the LPD Desa Adat Kedonganan, Krura was launched to help the krama of Kedonganan Adat Village who do not yet have their own homes and also to save land or palemahan Bali from investors and foreign parties, (2) the Krura program is intended for krama mipil Kedonganan Adat Village with steps to fill in forms and requirements, then the selection and determination of Krura recipients to the signing of the agreement and handover, and (3) the Krura program has a good impact on krama Kedonganan Adat Village because they can have their own house at a low price.